An in-depth spectroscopic examination of molecular bands from 3D hydrodynamical model atmospheres: II. Carbon-enhanced metal-poor 3D model atmospheres - Gallagher, Andrew J.; Ludwig, Hans-Günter; Homeier, Derek (Arxiv, 2017)
Context. Tighter constraints on metal-poor stars we observe are needed to better understand the chemical processes of the early Universe. Computing a stellar spectrum in 3D allows one to model complex stellar behaviours, which cannot be replicated in 1D. Aims. We examine the effect that the intrinsic CNO abundances have on a 3D model structure and the resulting 3D spectrum synthesis. Methods. Model atmospheres were computed in 3D for three distinct CNO chemical compositions using the CO 5 BOLD model atmosphere code, and their internal structures were examined. Synthetic spectra were computed from these models using Linfor3D and they were compared. New 3D abundance corrections for the G-band and a selection of UV OH lines were also computed. Results. The varying CNO abundances change the metal content of the 3D models. This had an effect on the model structure and the resulting synthesis. However, it was found that the C/O ratio had a larger effect than the overall metal content of a model. Conclusions. Our results suggest that varying the C/O ratio has a substantial impact on the internal structure of the 3D model, even in the hot turn-off star models explored here. This suggests that bespoke 3D models, for specific CNO abundances should be sought. Such effects are not seen in 1D at these temperature regimes.